Romeo: A system for more flexible binding-safe programming*. (22nd July 2016) - STANSIFER, PAUL; WAND, MITCHELL
Abstract: Current systems for safely manipulating values containing names only support simple binding structures for those names. As a result, few tools exist to safely manipulate code in those languages for which name problems are the most challenging. We address this problem with Romeo, a language that respects α-equivalence on its values, and which has access to a rich specification language for binding, inspired by attribute grammars. Our work has the complex-binding support of David Herman's λm, but is a full-fledged binding-safe language like Pure FreshML.